The Impact of Microplastics on Arbuscular Mycorrhzal Symbiosis in Plants (Solanum lycopersicum): A Literature Review - Putri Rahmadhani; R. Susanti; Talitha Widiatningrum (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Microplastic (MP) contamination in agricultural soils is an emerging anthropogenic threat that disrupts the rhizosphere of horticultural crops. Arbuscular Mycorrhizal Fungi (AMF) play an important role in improving nutrient uptake and stress resilience in tomato (Solanum lycopersicum), but their symbiotic relationship may be impaired by plastic residues. This literature review aims to synthesize the mechanisms by which microplastics disrupt AMF–tomato symbiosis and their implications for plant growth and productivity. A narrative-systematic literature review was conducted using Google Scholar, Scopus, and PubMed, covering publications from 2018–2026. Twenty-five relevant scientific articles were selected based on predefined inclusion and exclusion criteria. The synthesis indicates that microplastics act as physical and chemical stressors in the rhizosphere. Physically, they alter soil porosity and may damage extraradical AMF hyphae, while chemically, released additives can interfere with root–fungus signaling and reduce mycorrhizal colonization. These disruptions may impair arbuscule formation, water and nutrient acquisition, particularly phosphorus and zinc, and consequently reduce plant biomass and productivity. Reduced AMF protection may also increase tomato susceptibility to soil-borne pathogens such as Fusarium. Under severe contamination, nanoplastics may potentially enter root vascular tissues and raise concerns regarding food safety. Overall, microplastic pollution can weaken the ecological functions of AMF–tomato symbiosis and threaten sustainable tomato production.